COVID‐19‐induced granulomatosis with polyangiitis: A case report of a 16‐year‐old East Asian and literature review - Rong Jiang; Haibo Zhou; Long Wen; Xianglong Kong; Zhiguo Zhou (Immunity, Inflammation and Disease)
Abstract Objective Antineutrophil cytoplasmic antibody (ANCA)‐associated vasculitis (AAV) is divided into granulomatosis with polyangiitis (GPA), microscopic polyangiitis, and eosinophilic GPA. It is one of the most severe and potentially fatal autoimmune inflammatory conditions. The etiology and pathology of AAV are complex and poorly understood. Since the onset of the Coronavirus Disease 2019 (COVID‐19) pandemic, numerous reports have documented GPA cases following COVID‐19, suggesting a potential link between COVID‐19 and the development of GPA. This case report discusses a 16‐year‐old East Asian boy who developed GPA with diffuse alveolar hemorrhage after contracting COVID‐19. Additionally, a literature review was conducted to gain a deeper understanding of this disorder. Methods The study involved a retrospective analysis of the data of a case of GPA post‐COVID‐19 infection, aiming to summarize the clinical characteristics of GPA post‐COVID‐19 infection through a search of databases (PubMed, Wanfang Data, and CNKI), supplemented by standard searches in Google Scholar, Cochrane, Scopus, and LitCovid, and to conduct a comprehensive analysis of the literature. Results A total of 12 cases were identified and, when combined with the present case, yielded 13 cases of GPA post‐COVID‐19 infection, comprising 5 males and 8 females with an average age of (40.6 ± 19.5) years. The interval between COVID‐19 infection and the diagnosis of GPA varied from 1 day to 3 months across all cases. Mortality was reported at 7.7% (1/13). The most common clinical manifestations included cough (69.2%) and dyspnea (46.1%). Computed tomography scans revealed ground‐glass opacities and multifocal pulmonary nodules. In all cases, positive findings for c‐ANCA and protease 3‐antibody were observed. Renal involvement was observed in more than half of the patients.